STRATEGI MANAJEMEN WISATA RELIGI DI KALIMANTAN TIMUR (STUDI KASUS MAKAM TUNGGANG PARANGAN) - Hidayah, Nur; Noorthaibah, Noorthaibah; Nur, Nelvy Paulina (Fakultas Ushuluddin, Adab, dan Dakwah UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Religious tourism was a religious activity that intends to visit historical places. This activity also aimed to get closer to Allah SWT. This religious tourism object expected to invite many tourist interests because there layed person who was loved by Allah. The object was grave of Datu Tunggang Parangan located in Kutai Lama village, East Borneo. There was a history, where this cleric was the first cleric that entered Borneo. The purpose of this research was to make an effort to introduce one of the religious tourism object, and also apply the management strategy to promote the site of Datu Tunggang Parangan in order to get more visitors. The effort by marketing strategy either social media or verbally. Besides, there are also Erau, a cultural attraction that held and became a main attraction in Kutai Kartanegara. Therefore, this cultural attraction can assist to invite many people to visit the grave of Datu Tunggang Parangan. The data collection technique were interview and documentation. Keyword: Management Strategy, Religious Tourism.